Perkembangan pemikiran ekonomi dan munculnya pandangan strukturalis - Hamid, Edy Suandi (Economic Journal of Emerging Markets, 2016)
In the social sciences, economics is considered as the most progressive and dynamic science. Economics has a complete analysis tool, which combines both qualitative and quantitative approaches. In its process, the dynamics of economics is indicated by the emerge of new view with different approaches.